2023
DOI: 10.3389/fpubh.2022.962259
|View full text |Cite
|
Sign up to set email alerts
|

Association between social supports and negative emotions among pediatric residents in China: The chain-mediating role of psychological resilience and burnout

Abstract: BackgroundChinese pediatricians are facing challenges, and there is a need to examine the issue of negative emotions, namely, stress, anxiety and depression, among front-line pediatric residents in clinical settings. Understanding the current situation and influencing factors of negative emotions among pediatric residents in China and exploring the formation mechanism can lay a foundation for psychological interventions.MethodsA total of 138 pediatric residents in the Children's Hospital, Zhejiang University S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…These negative events require a strong psychological resilience to adopt appropriate solutions. Higher levels of psychological resilience are associated with the generation of positive emotions and attitudes, such as optimism, hope, and satisfaction, which enable the oldest-old to quickly recover from adversities, thus enhancing their desires to survive ( 39 ). Therefore, we recommend the public enhance routine monitoring of the psychological resilience of the oldest-old, to identify any existing resilience-related issues promptly, and to implement targeted interventions to improve their psychological well-being and enhance their chances of longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These negative events require a strong psychological resilience to adopt appropriate solutions. Higher levels of psychological resilience are associated with the generation of positive emotions and attitudes, such as optimism, hope, and satisfaction, which enable the oldest-old to quickly recover from adversities, thus enhancing their desires to survive ( 39 ). Therefore, we recommend the public enhance routine monitoring of the psychological resilience of the oldest-old, to identify any existing resilience-related issues promptly, and to implement targeted interventions to improve their psychological well-being and enhance their chances of longevity.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that psychological resilience played a protective role in survival outcomes for the oldest-old in China. The oldest-old often face various sources of stress, such as health issues related to physical frailty, economic burdens associated with caregiving, and social isolation (37,38). These negative events require a strong psychological resilience to adopt appropriate solutions.…”
Section: Discussionmentioning
confidence: 99%